Description of pharmacists' reported interventions to prevent prescribing errors among in hospital inpatients: a cross sectional retrospective study - Abdulhakim A. Alzahrani; Monira M. Alwhaibi; Yousif A. Asiri; Khalid M. Kamal; Tariq M. Alhawassi (BMC, 2021)
Abstract Background Prescribing errors (PEs) are a common cause of morbidity and mortality, both in community practice and in hospitals. Pharmacists have an essential role in minimizing and preventing PEs, thus, there is a need to document the nature of pharmacists' interventions to prevent PEs. The purpose of this study was to describe reported interventions conducted by pharmacists to prevent or minimize PEs in a tertiary care hospital. Methods A retrospective analysis of the electronic medical records data was conducted to identify pharmacists' interventions related to reported PEs. The PE-related data was extracted for a period of six-month (April to September 2017) and comprised of patient demographics, medication-related information, and the different interventions conducted by the pharmacists. The study was carried in a tertiary care hospital in Riyadh region. The study was ethically reviewed and approved by the hospital IRB committee. Descriptive analyses were appropriately conducted using the IBM SPSS Statistics. Results A total of 2,564 pharmacists' interventions related to PEs were recorded. These interventions were reported in 1,565 patients. Wrong dose (54.3 %) and unauthorized prescription (21.9 %) were the most commonly encountered PEs. Anti-infectives for systemic use (49.2 %) and alimentary tract and metabolism medications (18.2 %) were the most common classes involved with PEs. The most commonly reported pharmacists' interventions were dose adjustments (44.0 %), restricted medication approvals (21.9 %), and therapeutic duplications (11 %). Conclusions In this study, PEs occurred commonly and pharmacists' interventions were critical in preventing possible medication related harm to patients. Care coordination and prioritizing patient safety through quality improvement initiatives at all levels of the health care system can play a key role in this quality improvement drive. Future studies should evaluate the impact of pharmacists' interventions on patient outcomes.